Melihat resiliensi karyawan dari kecerdasan emosi dan efikasi diri - Tiana, Ade Amelia Siska; Rini, Rr Amanda Pasca; Lestari, Bawinda Sri (PSYCOMEDIA : Jurnal Psikologi, 2025)
Resilience is an individual's ability to bounce back after experiencing stress or difficult situations in the work environment. Emotional intelligence and self-efficacy are thought to play a significant role in shaping this psychological resilience. This study aims to determine the relationship between emotional intelligence and self-efficacy with employee resilience. This study used a quantitative approach with a correlational method. The subjects in this study were employees working at PT Kharisma SF Sidoarjo. The sampling technique used was simple random sampling with a population of 250 people. Referring to the Krejcie & Morgan table, 150 participants were obtained. The instruments used in this study included an emotional intelligence scale, a self-efficacy scale, and a resilience scale. Data analysis was performed using multiple linear regression analysis techniques. The results showed a highly significant positive relationship between emotional intelligence and self-efficacy with employee resilience. This finding demonstrates the importance of developing emotional intelligence and self-efficacy as supporting factors for psychological resilience in the workplace.